Strategi Coping Religius Guru Wanita dalam Menghadapi Konflik Peran Ganda - Rizki Hadirah; Emilia Mustary; Muhammad Haramain; Astinah Astinah (Journal of Society Counseling, 2026)
This study aims to determine the form of dual role conflict, the form of religious coping, and the impact of religious coping on female teachers at UPTD SD Negeri 7 Parepare. The research uses a qualitative approach of phenomenology type to understand the experience of female teachers in carrying out their roles as educators and housewives. The research subjects consisted of four female teachers who were selected purposively. Data collection was carried out through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model. The results of the study showed that dual role conflicts include time-based conflict in the form of difficulty dividing time between work and family, behavior-based conflict in the form of difficulty adjusting professional behavior and domestic roles, and strain-based conflict in the form of physical fatigue and emotional stress due to carrying out two roles simultaneously. The forms of religious coping used include benevolent religious reappraisal, collaborative religious coping, seeking spiritual support, religious purification, and spiritual connection. The impact of religious coping is reduced stress and anxiety, increased self-resilience, emotional regulation, inner peace, and better social relationships. This study shows that religious coping plays an important role in helping female teachers cope with dual role conflicts and maintain psychological well-being. Theoretically, this study expands on the concept of religious coping from Kenneth I. Pargament in the context of female teachers in Indonesia, while practically, this research is relevant because the majority of elementary school teachers in Indonesia are women who are vulnerable to multiple role conflicts.